COMPARATIVO DO CICLO DE VIDA ENERGÉTICO DO SISTEMA DE CONCRETO E PVC COM O SISTEMA DE ALVENARIA CONVENCIONAL - Barros, Laís; Lira, Júlia; Miranda, Luiza; Ferreira, Karyne (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
A new construction system of concrete and PVC is being implemented in Brazil due to its rapid execution and rationalization of the materials. The system consists on modulated profiles according to the design, reducing the consumption and waste in the construction, and not needing finishing. Due to these positive characteristics, it was raised the hypothesis of this system to be more sustainable than the conventional masonry in ceramic blocks. Thus justifying its use in the national project "My house my life", in which thousands of popular houses are built quickly. However, an analysis is needed, to perceive if this system reduces the consumption of energy and emissions, and if its replacement by the conventional system is really viable. An energy life cycle analysis was performed comparing the concrete and PVC systems, thickness of 150 mm, with conventional masonry. Although the market offers profiles of different thickness, only this one meets all the requirements of the Brazilian standard NBR 15220 with respect to the thermal performance for Brasília, bioclimatic zone 4. It was concluded that the concrete and PVC system is a sustainable solution, because it obtained an energy consumption and emissions almost half lower than the conventional masonry system.